2015
DOI: 10.4269/ajtmh.14-0758
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Genotyping of Coxiella burnetii in Ixodid Ticks in Oromia, Ethiopia

Abstract: Abstract. This study was conducted from September 2011 to March 2014 to address the occurrence and genotypes of Coxiella burnetii using molecular methods in ticks collected from domestic animals in Ethiopia. Ticks were tested for C. burnetii by quantitative real-time polymerase chain reaction (qPCR) targeting two different genes followed by multispacer sequence typing (MST). An overall prevalence of 6.4% (54/842) of C. burnetii was recorded. C. burnetii was detected in 28.6% (14/49) of Amblyomma gemma, 25% (31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
3
18
2
Order By: Relevance
“…C. burnetii was detected in a small percentage of ticks (5.5%) collected from sheep, goats, and cattle. The prevalence rate is comparable to the 6.4% reported in ticks collected from cattle in Ethiopia [ 26 ]. On the contrary, a study done in rural Western Kenya reported a lower prevalence of 2.5% in ticks collected from cattle [ 27 ] where zero grazing is commonly done.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…C. burnetii was detected in a small percentage of ticks (5.5%) collected from sheep, goats, and cattle. The prevalence rate is comparable to the 6.4% reported in ticks collected from cattle in Ethiopia [ 26 ]. On the contrary, a study done in rural Western Kenya reported a lower prevalence of 2.5% in ticks collected from cattle [ 27 ] where zero grazing is commonly done.…”
Section: Discussionsupporting
confidence: 76%
“…pulchellus and A. gemma tick species. C. burnetii infection in these two tick species has been reported before in Ethiopia [ 26 ] while C. burnetii infection in Rh. pulchellus was recently reported in Kenya [ 18 ].…”
Section: Discussionmentioning
confidence: 83%
“…In line with our findings, previous reports showed that the risk of Q fever infection is greatest in animals with a high rate of tick infestation (Asadi et al 2014 ; Cantas et al 2011 ; Psaroulaki et al 2006 ). In addition, molecular surveys (based on PCR amplification, reverse line blot hybridisation and deoxyribonucleic acid [DNA] sequencing) reported the presence of C. burnetii DNA in ticks collected from different domestic ruminants (Aouadi et al 2017 ; Kumsa et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reported a high seroprevalence of C. burnetii, (31.6% in cattle, 90.0% in camels and 54.2% in goats). A 6.4% prevalence of C. burnetii in Ethiopia was also report from different Ixodid ticks species by quantitative real time polymerase chain reaction targeting two different genes followed by multi-spacer sequence typing (MST) by [28].…”
Section: Introductionmentioning
confidence: 91%